The Polar® OH1 optical heart rate sensor is valid during moderate-vigorous exercise - Schubert, M. M.; Clark, A.; De La Rosa, A. B. (Sports Medicine International Open, 2018)
Purpose Traditional heart-rate monitoring through the use of electrocardiograms or chest-worn heart rate sensors can be challenging in certain sports or in field settings. New technologies, such as photoplethysmography (PPG), have enabled heart-rate monitoring at alternate sites. However, to date, the accuracy and validity of various PPG sensors has not been examined in detail. The purpose of the present investigation was to determine the validity of an arm-worn PPG sensor during yoga sequences.